Metaphysical Conflict. A Study of the Major Novels of Ivan Turgenev - Woodward, James B. (Slavistische Beitraege, 1990)
Written between 1855 and 1862, the four novels "Rudin", "A Nest o f the Gentry", "On the Eve" and "Fathers and Sons" are generally recognised as Turgenev's most notable contribution to Russian and world literature. Are they primarily social chronicles, as Turgenev suggested, or are they rather to be seen as celebrations of life, of the beauty of love and youthful idealism? Are they paens to the nobility of the human spirit or ironic comments on human folly? The same questions are addressed in the present study, but the question with which it is principally concerned is that of the novels' essential character.